PENGARUH PENGUASAAN KOSAKATA DAN STRUKTUR KALIMAT TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI BAHASA INGGRIS - Novani Puspitasati (INFERENCE: Journal of English Language Teaching, 2021)
The purpose of this research is to find out: 1). The effects of vocabulary mastering and sentence structure towards English exposition writing skills. 2). The effects of vocabulary mastering towards English exposition writing skills. 3). The effects of sentence structures on English exposition writing skills. The research method used is a survey with double linear regression analysis—the study sample has as many as 93 students, which are taken using a proportional and simple random sampling technique. The statistics test is using the F test. The result showed that: 1). There are significant effects of vocabulary mastering and sentence structure towards English exposition writing skills at State Vocational Schools in Tangerang. That is proved by Sig = 0.000 <0.05 and F observe = 38.543. 2). The effects of vocabulary mastering towards English exposition writing skills, presented by Sig = 0.000 < 0.05 and t observe = 3.779. 3). There are significant effects of sentence structures on English exposition writing skills at State Vocational Schools in Tangerang. It is proven by Sig = 0.000 < 0.05 and t observe = 4.331.Keywords: vocabulary mastering, sentence structure, English exposition writing skills.